(untitled) (Revista científica Olimpia, 2019)
The adapted physical activity constitutes a tool of primordial for the attention of people with SEN and/or disabled. Authors like E. Oña (2002); M. García & Col (2005); A .Molina & F. Garza (2006); J. Salazar (2007) and L. Figueredo (2006, 2011) in their investigations, they offer treatment to the development and invigoration of the organism from the practice of the Adapted Physical Activity, like part of the preparation for their mature life, that which constitutes the objective of this development area, however, is insufficient their theoretical treatment as integrative process and personalized according to their diagnosis. In their majority, these authors, focalize their efforts in and from the school curriculum, what limits the physical development and of the rest of the areas, alone to the context of the school. Doubts that the school is an important place doesn’t fit where the scholar passes great part of his time; however, other spaces and other intervention strategies that contribute, not only big benefits to the physical area, but also to the rest of the development areas like it is the case of the Hypo therapy.